Toxicokinetic studies of sodium nitrite in goats following intravenous and oral administration - KAUR, N.; PRAMANIK, A K; BISWAS, U; MANDAL, T K (The Indian Journal of Animal Sciences, 2014)
Black Bengal goats Were given sodium nitrite as a minimum single toxic intravenous(30 mg/kg) and oral (50 mg/kg) dose to induce minimum toxicity and toxicokinetic parameters and haemoglobin and methaem6globin levels were estimated. The maximum and minimum plasma concentration of nitrite were 001±0.03 and 0.001±0.0001 mM at 0.08 hr following intravenous injection while these values of nitrate were 1.49 ±0.14 and 0.00 1±0.0002 mM at 0.08 and 24 hr respectively. The elimination half-lives (t1/2 B) of nitrite was shorter compared to nitrate in goats. The maximum plasma concentration of nitrite appeared at 1 hr and that of nitrate at the same hour after single oral dose of sodium nitrite. The minimum plasma concentration of nitrite and nitrate were detected at 12 and 36 hr respectively. The study suggested that sodium nitrite was oxidized to nitrate resulting in lower concentration of nitrite compared to nitrate though sodium nitrite was adminIstered in goats.